2011
DOI: 10.4061/2011/302406
|View full text |Cite
|
Sign up to set email alerts
|

Anti-A and Anti-B Haemolysins amongst Group “O” Voluntary Blood Donors in Northeastern Nigeria

Abstract: . One thousand nine hundred and twenty nine voluntary group "O" blood donors (1609 males and 320 females, median age 26 years ± 7.6 SD) were screened for alpha-(anti-A) and beta-(anti-B) haemolysins using the standard tube technique at 37 degrees C for 1 hour. All samples showing haemolysis were titrated for anti-A and anti-B haemolysins. Results. The overall prevalence of haemolysins in group O donors was 55.4%. Prevalence of alpha-and beta-haemolysins only was 10.3% and 12.6%, respectively, while that of don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 6 publications
4
17
1
Order By: Relevance
“…[13,16] This finding is similar to that reported by Adewuyi et al among black Zimbabweans [6] but higher than that reported by Olawumi and Olatunji who found a significant prevalence titre of 2.0% for anti-A and 2.8% for anti-B [8] and Kagu et al that found prevalence of 0.4% for anti-A and 0.2% for anti-B. [17] Such difference may be explained by the large sample size used by Kagu et al compared with that used in this study. Another explanation for the difference could be the addition of adsorbed fresh O serum to the test serum by Olawumi and Olatunji and Kagu et al While this was meant to serve as a source of complements, the adsorbed fresh O serum will dilute the serum and may lead to a reduction in the titers obtained.…”
Section: Discussionsupporting
confidence: 84%
“…[13,16] This finding is similar to that reported by Adewuyi et al among black Zimbabweans [6] but higher than that reported by Olawumi and Olatunji who found a significant prevalence titre of 2.0% for anti-A and 2.8% for anti-B [8] and Kagu et al that found prevalence of 0.4% for anti-A and 0.2% for anti-B. [17] Such difference may be explained by the large sample size used by Kagu et al compared with that used in this study. Another explanation for the difference could be the addition of adsorbed fresh O serum to the test serum by Olawumi and Olatunji and Kagu et al While this was meant to serve as a source of complements, the adsorbed fresh O serum will dilute the serum and may lead to a reduction in the titers obtained.…”
Section: Discussionsupporting
confidence: 84%
“…A case of severe fetal anemia due to ABO incompatibility caused by high anti-B IgG titers of African mother was reported (11). The high frequency of hemolysins in group O blood donors was commonly found in Nigerian and Indian populations with the prevalence ranging from 23.2% to 62.8% (12)(13)(14)(15). A previous study of ABO antibody levels among Japanese, Lao, and Thai blood donors in 2006 showed that IgM anti-A and anti-B titers were low in Thais, similar to the Japanese antibody titers reported in 2001, but IgG anti-A and anti-B titers were high, similar to those reported in Japanese in 1986 (16).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of complement in immunohematology, most laboratory methods avoid seeing its hemolytic effects due to the use of plasma, where the chelating properties of anticoagulants also inhibit the complement cascade . However, there are several immunohematologic assays including the detection of ABO hemolysins in blood donors, autoimmunity studies, transfusion and drug reaction investigations, and complement deficiency, where involvement of the human complement cascade is still measured. In vitro deposition of complement on red blood cells (RBCs) can also be used to enhance the immunological reactions of some antibodies, particularly those within the Kidd, Kell, and Lewis blood group systems .…”
Section: Comparison Of Methods Between Studies Of Polley and Mollison mentioning
confidence: 99%